Implementation strategy of telecom operators’ data lake technology - Junjun HU; Xiaojun XIE; Yanbin SHI; Qi YU (Dianxin kexue)
Firstly,the traditional data architecture of telecom operators was analyzed and the problems such as low quality,lack of real-time,lack of flexibility and mutual constraints of storage and application were identified.Then,the feasibility of introducing data lake technology was discussed,the storage scale and low cost of data lake,the originality of data and ease of use,and the application of on-demand modeling were clarified,which could provide great benefits for telecom operators’ data architecture optimization.Finally,the data lake construction plan of unified storage,unified standards,near-source acquisition,and application separation was proposed,and key points such as data lake data partitioning,deployment,lake entry and application data dynamic loading,and unified data management were clearly stated.